The therapeutic potential for targeting CSE/H2S signaling in macrophages against Escherichia coli infection - Shaodong Fu; Zhenglei Wang; Xiangan Han; Yuanyuan Xu; Jinfeng Miao (Veterinary Research, 2023)
Abstract Macrophages play a pivotal role in the inflammatory response to the zoonotic pathogen E. coli, responsible for causing enteric infections. While considerable research has been conducted to comprehend the pathogenesis of this disease, scant attention devoted to host-derived H2S. Herein, we reported that E. coli infection enhanced the expression of CSE in macrophages, accompanied by a significantly increased inflammatory response. This process may be mediated by the involvement of excessive autophagy. Inhibition of AMPK or autophagy with pharmacological inhibitors could alleviate the inflammation. Additionally, cell model showed that the mRNA expression of classic inflammatory factors (Il-1β, Il-6), macrophage polarization markers (iNOS, Arg1) and ROS production was significantly down-regulated after employing CSE specific inhibitor PAG. And PAG is capable of inhibiting excessive autophagy through the LKB1-AMPK-ULK1 axis. Interestingly, exogenous H2S could suppress inflammation response. Our study emphasizes the importance of CSE in regulating the macrophage-mediated response to E. coli. Increased CSE in macrophages leads to excessive inflammation, which should be considered a new target for drug development to treat intestinal infection.